Serum glial cell line-derived neurotrophic factor: a potential biomarker for white matter alteration in Parkinson’s disease with mild cognitive impairment - Liu, Yi; Xu, Yan; Tong, SuYan (Frontiers in Neuroscience, 2024)
ObjectiveMild cognitive impairment (MCI) is a common non-motor manifestation of Parkinson’s disease, commonly referred to as PD-MCI. However, there is a lack of comprehensive data regarding the role of glial cell line-derived neurotrophic factor (GDNF) and cerebral white matter damage in the pathogenesis of PD-MCI. The objective of this study is to investigate the association between alterations in GDNF levels and cerebral white matter damage in individuals diagnosed with PD-MCI, as well as to explore their potential involvement in cognitive progression.MethodsNeuropsychological assessments were conducted on 105 patients with Parkinson’s disease and 45 healthy volunteers to examine various cognitive domains. An enzyme-linked immunosorbent assay (ELISA) was employed to measure serum levels of GDNF. Additionally, all participants underwent 3.0T magnetic resonance imaging (MRI) to acquire diffusion tensor images (DTI), and a voxel-based analysis (VBA) approach was utilized to compare the fractional anisotropy (FA) values of white matter in the brain.ResultsThere was a significant correlation between the right corpus callosum, right cingulate gyrus, and the Digit Span Backward Test (DSB-T) as well as the Trail Making Test A (TMT-A), both of which assess attention and working memory functions. The left internal capsule exhibited a significant correlation with the Trail Making Test B (TMT-B) and the Clock Drawing Test (CDT), which evaluate executive function. Additionally, the right cingulate gyrus showed a significant association with scores on the Auditory Verbal Learning Test-HuaShan (AVLT-H), assessing memory function. Abnormal fiber structures that demonstrated significant correlations with serum GDNF levels included the left internal capsule, left corticospinal tract, right corpus callosum, and right cingulate gyrus.ConclusionThe decrease in serum GDNF levels among PD-MCI patients exhibiting impairments in attention and working memory function was significantly correlated with alterations in the corpus callosum (knee) and posterior cingulate gyrus. Furthermore, the reduction of serum GDNF levels in PD-MCI patients with impaired executive function is associated with changes in the internal capsule (forelimb) projection fibers. Additionally, the decline of serum GDNF levels in PD-MCI patients experiencing memory function impairment is related to alterations in the right cingulate gyrus.